Pandemija Covida-19 kot nadaljevanje procesov fleksibilizacije in prekarizacije delovnih razmer za kreativne poklice v Sloveniji - Uršič, Matjaž (Teorija in praksa, 2021)
The analysis of creative activities often reveals problematic observations with regard to the work processes of creative employees. From this point of view, creative workers are perceived as being very flexible in terms of payment, workplace and type of work. Such characteristics mean creative professions are not classified as a traditional or economically and socially more stable form of employment. We may thus assume that creative workers have been among the worst affected by the Covid-19 pandemic. Using data from the longitudinal research "Slovenian cultural and creative worker in the Covid-19 period" (2020), the article first analyses the pandemic's effects on the wider creative sector and, second, identifies elements of change in the work process and living conditions of creative workers that have led to the precarisation of specific individual creative subsectors like visual, performing arts or music. The findings show in most segments of creative professions the pandemic has added to the existing forms of precarisation.
Keywords: Covid-19; Delo na domu; Epidemics; Epidemije; fleksibilizacija; Home labor; kreativne industrije; kreativni delavec; prekarizacija